Lateral drift of photo-generated charge carriers in the p-SiGe/Si heterostructures with quantum wells - Gudenko1, Yu.M.; Vainberg, V.V.; Poroshin, V.M.; Tulupenko, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The drift of charge carriers in the p-Si₀.₈₈Ge₀.₁₂/Si heterostructures under strong lateral electric fields and conditions of carrier generation by the band-to-band light absorption has been investigated experimentally. The data of the drift length, drift mobility, and lifetime of charge carriers within the temperature range 20 to 77 K under the electric field up to 1500 V/cm are presented.